Strategic alignment maturity assessment on conventional bank’s information technology - Nia Budi Puspitasari; Singgih Saptadi; Aditya Dwi Rahmadi (Faculty of Engineering, Universitas Negeri Yogyakarta, 2022)
Strategic alignment between information technology and business strategy is needed to achieve an organization's performance excellence. Bank X is a bank that focused on serving the micro, small and medium enterprise (MSME) market segments. Bank X provided a variety of banking services which are generally grouped into activities of raising and distributing funds. Banking services are carried out conventionally. At the end of 2019, Bank X was acquired by an investment holding company. The objective of the acquisition is to develop Bank X into a bank with a digital platform. This study aims to measure the maturity level of strategic alignment of information technology with business strategies at Bank X. A conceptual framework is developed based on relevant literature. The level of strategic alignment is measured based on Luftman's Strategic Alignment Maturity Model (SAMM) framework. The results of the analysis show that the strategic alignment maturity level of Bank X is at level 3. Several recommendations are given to improve the maturity level of Bank X's strategic alignment.